Nest tree characteristics of the Lesser Spotted Woodpecker (Dendrocopos minor) in boreal forest landscapes - Pakkala, Timo; Tiainen, Juha; Pakkala, Heikki; Piha, Markus; Kouki, Jari (BirdLife Suomi, 2019)
Tree cavities, and especially cavities made by woodpeckers, are important microhabitats in forest ecosystems. However, the properties of woodpecker nest trees and cavities are poorly known even in boreal areas where most tree cavities are made by woodpeckers. We studied the nest tree characteristics of the Lesser Spotted Woodpecker (Dendrocopos minor) in a 170-km2 forest-dominated area in southern Finland during 1987–2018. The data included 97 nest trees with 106 nest cavities in five deciduous tree species. During the study period, more than one nest cavity (2–3) was excavated in 7% of all cavity trees. Nests were found in three forest types, but the proportions of nest tree species differed between them. Birch (Betula spp.) was the most common nest tree species with 40% of nests. Nest trees were either dead (79%) or decaying (21%), and the majority (69%) had a broken top. The mean diameter at breast height (DBH) of a nest tree was 24.7 cm and the mean height of a cavity hole was 3.3 m; size and height were significantly positively correlated. The mean ratio of cavity height in relation to the respective nest tree height was 0.49, and did not depend on the nest tree condition. The results highlight the importance of dead and decaying deciduous trees as nest cavity sites for this small woodpecker species. Provision of suitable cavity trees during forest management is important to maintain breeding and cavity building opportunities for the Lesser Spotted Woodpecker in managed forests.
Keywords: Nest tree species; Nest tree quality; Nest tree size; Nest tree condition; Nesting habitat